Developing and investigating copper and iron chalcogenide nanoparticle syntheses to elucidate the underlying processes of formation - Moloney, Lily June, author; Prieto, Amy L., advisor; Sambur, Justin, committee member; Krummel, Amber, committee member; Buchanan, Kristen, committee member (Colorado State University. Libraries, 2021)
Nanoparticle technology is rapidly growing field due to the unique, tunable properties of nanoparticles (NPs) as compared to their bulk counterparts, enabling a wide range of new applications. The key step, however, to applying NP systems to new areas is developing high quality syntheses. Specifically, solution-based methods for synthesizing NPs offer many synthetic handles for tuning structure/property relationships by controlling composition, size, morphology and capping agents. To effectively design syntheses to control the resulting properties, in depth investigation of the underlying fundamental processes are required. Elucidation of these processes would allow trends to be illuminated and a toolkit of synthesis methods could be built. However, a myriad of interactions (organic, inorganic, solid-state) occur during these reactions, and often these interactions are intertwined with each other. Therefore, careful examination of nanoparticle synthesis for various systems are necessary to advance the NP field. In Chapter 1, we review literature reports that exemplify the careful examination of underlying mechanisms and pathways required for developing synthesis methods that allow for control over composition, size, morphology. This chapter is split into two major sections; 1) balancing precursor reactivities and elucidating mechanisms and 2) understanding reaction pathways. The first section is split into anion and cation speciation/reactivity. The anion section focuses on the development of chalcogenide reactivity trends and how these trends have led to advanced nanoparticle control. The cation section considers the use of metal-amide complexes to increase and balance reactivities of cations to produce small, phase pure NPs. In depth mechanism studies of these metal-amide reactions in model unary and binary system led to the utilization of this reagent in more complex ternary systems. The second section focuses on investigation of reaction pathways, discussing how exploration of the reaction phase space as well as determination of intermediates is important for achieving a full picture. We end with a brief discussion on the importance of thorough characterization for describing these reaction mechanisms and pathways accurately. The importance of investigating the reaction pathway was inspiration for the research described in Chapter 2. Few solution-based techniques to synthesize Cu3Si, a material with applications in electronics, batteries, and photovoltaics, exist. This could stem from the limited number of Si precursors viable in solution-based techniques. This led us to explore the reaction between Mg2Si and CuCl2 in oleylamine, as a solution-based metathesis route to form Cu3Si particles. The reaction pathway and the role of the solvent were characterized and elucidated. It was found that the reaction proceeds through a two-step pathway, where a Si matrix, Cu particles, and MgCl2 initially form. Then, the Cu particles diffuse into the Si matrix to form Cu3Si particles encased in a Si matrix (Cu3Si@Si matrix). Additionally, various solvents are tested to understand the importance of the solvent for the reaction to proceed successfully. The coordinating ability of the solvent was important, where an overly non-coordinating or coordinating solvent limited the production of Cu3Si@Si matrix particles. Oleylamine was found to be a “goldy-locks” solvent as the coordination supported both steps of the reaction. In Chapter 3, the mechanistic metal-silylamide studies described in Chapter 1 offered inspiration. Specifically, Rebecca C. Miller in our group was recently able to synthesize Fe2GeS4 by utilizing lithium bis(trimethylsilyl)amide (LiHMDS). The increased understanding of the Fe-Ge-S phase space and the role of the LiHMDS gained from this previous study led to the research presented in Chapter 3. In this chapter, we report the first nanoparticle synthesis of Fe2GeSe4 and Fe2GeS4-xSex (x = 0.8 and 1) via a LiHMDS-assisted hot-injection method. This system allowed the role of LiHMDS in balancing not only the cationic but also anionic species to be investigated. This was done by exploring the synthesis parameters, the pre-injection chalcogen speciation, and the reaction pathways. Finally, in Chapter 4, synthesis methods attempted toward Cu2SiSe3 formation are described and a future direction for this project is proposed. Copper-based chalcogenides have gained much attention due to their exemplary intrinsic and structural properties. Cu2SiSe3 has been theorized to be a potential photovoltaic material, yet a NP synthesis of this material has not been realized. Exploration of hot injection, metathesis, and solvothermal solution phase methods are reported. However, all efforts resulted in binary Cu/Se phases over the formation of the desired ternary. A future direction for this project could be instead focusing on investigating reactivity trends of the group IV elements, Si, Ge, and Sn, using an amide-assisted synthesis of the Cu2IVSe3 materials.